Effects of Withaferin A on Mouse Models of Alexander Disease - Lewis, Diana (My University, 2015)
Alexander disease is a rare neurodegenerative disorder which is caused by the accumulation of glial fibrillary acidic protein (GF AP) resulting in aggregates termed Rosenthal Fibers (RFs) in the central nervous system. TAR DNA-binding protein 43(TDP-43) is a DNA/RNA binding protein that is involved in the pathology of disorders such as amyotrophic lateral sclerosis (ALS) as well as Alexander disease. Withaferin A(WA) is a plant derivative and known inhibitor ofNF-Kl3, and activated NF-KB targets the GF AP promoter. We proposed that treatment of the mice with WA should downregulate the GFAP promoter. We treated 10 week old Alexander disease mutation GFAP knock-in mice with WA twice a week for 4 weeks. After treatment we analyzed the amount of GF AP protein concentration with an ELISA. Results showed an initial significant decrease in GF AP, but after repeating the experiment and analyzing specific brain regions, treatment was determined to be slightly toxic.